Formulasi Minuman Serbuk Instan Daun Jeruju (Acanthus ilicifolius L.) dengan Penambahan Sari Jahe Emprit (Zingiber officinale var. Amarum) yang Berpotensi Sebagai Pangan Fungsional - Apsari, I Gusti Ayu Renita Putri; Puspawati, Gusti Ayu Kadek Diah; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 4 (2024): Jurnal ITEPA, 2024)
Jeruju leaves are herbal plants belonging to the mangrove group. These leaves have been processed into loloh and instant powder drinks, but their taste and aroma have not yet been widely appreciated, despite jeruju leaves being reported to have potential as functional food. Enhancement of aroma and taste is achieved by adding emprit ginger, which possesses distinctive flavor and aroma characteristics. This research aimed to determine the effect of adding emprit ginger on instant powdered jeruju leaf drink characteristic, identify the right concentration of emprit ginger for the best characteristics, and evaluate its potential as a functional food. The research employed a completely randomized design (CRD) with emprit ginger addition of five levels (0%, 10%, 20%, 30%, and 40%), each replicated 3 times. Analysis of variance (ANOVA) and Duncan's multiple range test were used for analyzed data. The results showed adding emprit ginger significantly affected the yield, moisture content, ash content, total phenolic content, antioxidant activity, ?-glucosidase enzyme inhibition activity, solubility, dissolution time, and sensory attributes including color, aroma, taste, and overall acceptance of the instant powdered jeruju leaf drink. The addition of 40% emprit ginger produced the best drink, with a yield of 17.85% (w/w), moisture content of 2.73% (w/w), ash content of 1.53% (w/w), total soluble solids of 5.20 °Brix, total phenolic content of 13.68 mg GAE/100g, antioxidant activity of 69.64%, ?-glucosidase enzyme inhibition activity of 17.26%, solubility of 97.26%, dissolution time of 9.74 seconds, he color is liked, the aroma and taste are highly liked with characteristics of Jeruju leaves – typical of Emprit ginger, and the overall preference is liked. The instant powdered jeruju leaf drink with a 40% emprit ginger addition has potential as a functional food, offering ?-glucosidase enzyme inhibition and being rich in antioxidants. Keywords: jeruju leaf, emprit ginger, instant powder drink, ?-glucosidase enzyme